Income taxation : laws, principles and applications - Banggawan, Rex B. (Baguio City : Real Excellence Publishing, 2014)
Income taxation is the most complex form of taxation with vast and expanding rules and regulations. In view of this, the books devised a principle-based structural presentation of income taxation. This resulted in significant reduction of the vast tax rules into simple structures of the interconnected and arranged concepts intended to maximize clarify and support long-term concept retention.
Part I: Introductory concepts -- Part II: Income recognition, measurement and reporting and taxpayer classifications -- Part III: Special income taxation -- Part IV: Regular income taxation
Keywords: INCOME TAXATION -- PHILIPPINES